Assessing Digital Performance of Public Services in the EU: E-Governance and Technology Integration - Oana Ramona Lobonț; Cristina Criste; Alexandra Ioana Vintilă; Andreea Florentina Crăciun; Nicoleta Claudia Moldovan (Systems, 2025)
This research aims to rank the regions of the European Union based on their digital performance in public services, offering a new perspective on the digitalization process and its effects on the European public system. Therefore, the study examines the evolution of intensity and the impact of digitalization through the e-government framework, specifically from the perspective of the 27 member states of the European Union. Thus, the research analyzes the interplay between digital intensity, institutional quality, and adoptingadopting e-government services to understand the challenges and disparities across different regions. To evaluate the digital performance of the European Union regions, the analysis employs the following methods: (i) Principal Component Analysis to construct a composite Institutional Quality Index based on governance indicators, (ii) Gaussian graphical models to assess the relationships between digital intensity, institutional quality, and e-government highlighting the interconnections between variables, (iii) Data Envelopment Analysis to measure the relative efficiency of public service delivery, and (iv) cluster dendrograms to identify the clusters of countries with similar performance levels and challenges. The findings reveal disparities among nations and the contemporary challenges facing EU member states in implementing and adopting e-government initiatives. While Denmark and Finland often excel in digital service efficiency, countries like Bulgaria, Greece, and Romania may lag due to citizens’ limited digital infrastructure and digital literacy. However, it is to note that the quality of regulations, as reflected in the Institutional Quality Index, plays a significant role in successfully integrating digitalization. The study underscores the crucial role of digital adoption in enhancing the public sector’s performance, particularly when coupled with strong institutional frameworks.